2016
DOI: 10.1080/08990220.2016.1229178
|View full text |Cite
|
Sign up to set email alerts
|

Comparing test–retest reliability and magnitude of conditioned pain modulation using different combinations of test and conditioning stimuli

Abstract: This study aimed to compare the reliability and magnitude of conditioned pain modulation (CPM) by applying different test stimuli (TS) and conditioning stimuli (CS). Twenty-six healthy male participants were recruited in the study of two identical sessions. In each session, four TS (electrical, heat, handheld, and cuff pressure algometry) were applied before and during CS (cold pressor test (CPT) or cuff algometry). The same procedure was repeated with 45-min intervals, but with the other CS. Five thresholds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
1
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 52 publications
6
98
1
2
Order By: Relevance
“…CPM measurement is reliable, but varies depending on stimulation parameters and study methodology (Kennedy et al, 2016). The combination of heat pain test or handheld or cuff pressure pain and the cold pressor test (CPT) are reliable methods to induce CPM, whereas electrical and heat pain combined with cuff do not yield significant CPM effects (Gehling et al, 2016; Imai, Petersen, Mørch, & Arendt Nielsen, 2016; Petersen, Vaegter, & Arendt-Nielsen, 2017). …”
Section: Cpm Protocolsmentioning
confidence: 99%
“…CPM measurement is reliable, but varies depending on stimulation parameters and study methodology (Kennedy et al, 2016). The combination of heat pain test or handheld or cuff pressure pain and the cold pressor test (CPT) are reliable methods to induce CPM, whereas electrical and heat pain combined with cuff do not yield significant CPM effects (Gehling et al, 2016; Imai, Petersen, Mørch, & Arendt Nielsen, 2016; Petersen, Vaegter, & Arendt-Nielsen, 2017). …”
Section: Cpm Protocolsmentioning
confidence: 99%
“…Intersession reliability of CPM‐effects is good with interclass correlation coefficients (ICC) from 0.6–0.75, although the reliability depends on stimulation parameters, modality and protocols (Granovsky et al., ; Imai et al., ; Kennedy et al., ). Computerized pressure cuff algometry has excellent reliability over days (ICC > 0.8) (Graven‐Nielsen et al., ), both for unconditioned and conditioned test‐stimuli (Imai et al., ; Graven‐Nielsen et al., ). The cuff algometry CPM‐effect has also been reported with good reliability (Graven‐Nielsen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Impaired CPM‐effect has been linked to local painful conditions including knee pain (Arendt‐Nielsen et al., ; Rathleff et al., ) and widespread pain such as fibromyalgia (Julien et al., ; Potvin and Marchand, ; Gerhardt et al., ). Yet, some studies compare the conditioned test‐stimulus to a single, unconditioned test‐stimulus (Granovsky et al., , ; Imai et al., ; Vaegter et al., ) while others use an average of two or more test‐stimuli to compare with a single conditioned test‐stimulus (Rathleff et al., ; Stolzman and Bement, ; Stolzman and Hoeger Bement, ; Skovbjerg et al., ; Vaegter et al., ). Interestingly, a study showed that migraineurs loose the pain‐inhibitory effect of CPM when CPM‐paradigms are repeated in three bouts with 40 s intervals, suggesting that insufficiencies in the descending system may not be detected with single‐bout CPM assessment (Nahman‐Averbuch et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…There is significant variability in the magnitude of CPM (Imai et al., ; Kennedy et al., ), which may relate to age, sex (Edwards et al., ; Ge et al., ; Magerl et al., ) and other variables. One variable that has recently demonstrated a relationship with CPM is physical activity levels.…”
Section: Introductionmentioning
confidence: 99%